Crucial Cognitive Skills in Science Education: A Systematic Review - Hasanah, Uswatun; Shimizu, Kinya (Jurnal Penelitian dan Pembelajaran IPA, 2020)
This systematic review focuses on identifying three common cognitive skills in science education—process skills, critical thinking skills, and reasoning skills—in order to find the crucial skills in science education. The inclusion and exclusion criteria were created. In total, 78 articles published in 17 countries, namely the USA, Turkey, Indonesia, Malaysia, Iran, Palestine, Thailand, Nigeria, Jamaica, Israel, Kenya, Oman, Columbia, China, Philippines, Korea, Canada, were selected. The reviewed studies were published from 1998 to 2019. Fifty-seven studies were reported as journal publications and 21 studies came from conference proceedings. The results indicate that crucial skills exist such as science process skills (inference, measuring, identifying and controlling variable, definition operational variable, and explanation), critical thinking skills (interpreting data, inference, and evaluation), and reasoning skills (all subskills), and also revealed the relationship among them. This study concludes that the crucial skills in science education are mostly located in the reasoning skills domain.